Silver Nanoparticles - Fabrication, Characterization and Applications 2018
DOI: 10.5772/intechopen.76183
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Silver Nanoparticles Versus Chlorhexidine Against Streptococcus mutans and Lactobacillus casei

Abstract: The porpoise of the study was to evaluate the antibacterial effect of silver nanoparticles (Ag-NPs) versus chlorhexidine (CHX) against Streptococcus mutans and Lactobacillus casei. Three different reducing agents were used for the synthesis and characterization of Ag-NPs: sodium borohydride (NaBH 4), a chemical method, and Heterotheca inuloides (Hi) and Camellia sinensis (Cs), two eco-friendly methods. The synthesized substance was deposited on deciduous teeth. Its behavior in dental tissues was evaluated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…It is evident from recent reports that Chlorhexidine is being used less post-surgically due to interruption of fibroblast, and osteoblast activity which may delay wound healing activity at surgical sites [15]. Recent studies on silver nanoparticles have shown that they are comparable to Chlorhexidine's antimicrobial action even at lower concentrations than their quaternary ammonium counterparts [16]. Certain studies have even shown that silver nanoparticles can reduce inflammation around surgical sites leading to reduced healing time [17].…”
Section: Resultsmentioning
confidence: 99%
“…It is evident from recent reports that Chlorhexidine is being used less post-surgically due to interruption of fibroblast, and osteoblast activity which may delay wound healing activity at surgical sites [15]. Recent studies on silver nanoparticles have shown that they are comparable to Chlorhexidine's antimicrobial action even at lower concentrations than their quaternary ammonium counterparts [16]. Certain studies have even shown that silver nanoparticles can reduce inflammation around surgical sites leading to reduced healing time [17].…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that the biogenic AgNPs have improved activities compared to the chemically synthesized AgNPs and CHX. The chemical AgNPs were reduced by sodium borohydride (NaBH 4 ), and two green AgNPs were produced using extracts of Heterotheca inuloides (Hi) and Camellia sinensis (Cs) [124]. Hi produced smaller and more stable NPs when compared to Cs-AgNPs.…”
Section: Plant Extract-synthesized Agnps For Treatment Of Dental Dise...mentioning
confidence: 99%
“…The green AgNPs inhibited the growth of S. mutans and L. casei better than 2% CHX, while the smaller Hi-AgNPs had enhanced antibacterial activity compared to the Cs-AgNPs. [124].…”
Section: Plant Extract-synthesized Agnps For Treatment Of Dental Dise...mentioning
confidence: 99%
“…22201/ceiich.24485691e.2024.33.69816 Verónica Gasga Tapia, Aída Hamdan-Partida, Teresa Leonor Sánchez Pérez, Francisco Javier Martínez Ruiz, Jaime Bustos-Martínez Recientes investigaciones indican que soluciones antimicrobianas de AgNPs evitan la formación de biopelícula y actúan contra las principales bacterias cariogénicas. Se han evaluado formulaciones de AgNPs contra S. mutans con efectos antibacterianos (Misba et al, 2016;Schwass et al, 2018;Morales et al, 2018;Elgamily et al, 2018). Pérez-Díaz et al (2015) probaron la actividad antimicrobiana de las AgNPs contra un aislado clínico de S. mutans, encontrando una actividad antibiopelícula, contra S. mutans y presentaron compatibilidad con fibroblastos humanos.…”
Section: Introductionunclassified